Learning styles of Malaysian generation ‘Y’ healthcare undergraduates - Daud, Azlina; Nurumal, Mohd. Said; Shahadan, Siti Zuhaidah (2019)
Objective The learning styles of millennial students, also known as Generation ‘Y’, have been examined in the past to match the teaching style of an educator with the aim of improving behaviors, attitudes, and academic achievements. However, focus on Generation ‘Y’ healthcare undergraduates from a multi-cultural Asian society, is scarce and fragmented. Therefore, this research aims to identify the learning style preferences of Generation ‘Y’ undergraduates enrolled in varied healthcare programs at a Malaysian University. Method A quantitative cross-sectional study design was adopted. Honey and Mumford's Learning Style Questionnaire was used to explore the learning styles. Results The reflector learning style was most preferred by the Malaysian healthcare undergraduates, and no significant difference was found between the learning styles of the clinical group and the semi-clinical group. Conclusions Educators should engage Malaysian healthcare undergraduates in a non-threatening environment — Association between learning style and sociodemographic warrants further investigation.